Summaries of cases visited by the almoner - Cornish, F.
1901-12-30 1901 1900s 6 pages Wright — George & Percy 10371 - 2 Visited 13 Willow Walk and saw Mrs Lofty (or Lofthouse) Mrs. Wrights mother who said Mr Wright was a labourer but had only done 1 weeks work in 6 weeks, when at work he earned from 25/- to 30/- a week. He had belonged to a slate club but that had now finished. Mrs Lofty said Mr Wright took a glass of beer now and again but not often. Mrs. Wright goes out charing and washing she has two regular places to go every week and generally does 2 or 3 days casual work, by this means she earns on an average 10/- a week. There are 5 children none of whom are earning anything. They occupy a house the rent of which is 8/6 out of this they let 2 rooms one to a lodger for 2/6, the other to Mrs Lofty for 1/6 leaving them standing at 4/6. [Diabetes] Mrs. Sophia Lofty (or Lofthouse) states she has been an [inmate] in-patient in the G.N. Hospital suffering from wounds in her legs and has been an out-patient for some considerable time under Dr Stam the last time she attended was a month ago. She earns 5/- a week by charing of which she pays 1/6 to Mrs. Wright for her room. Mrs. Wright gives her a part of her food for looking after the children. Mrs. Lofty has applied to the Relieving Officer for outdoor relief but up to the present has had nothing from the parish. Diabetes & Tonsillitis Insufficient Infn Lush. Emma — 10331 Visited 37 Park Road saw Mrs. Lush who said her husband was a Farrier, but as work in that time was slack he was now working as a Carman for a firm in [ ] St., City, his wages were 25/- a week. The family consisted of Father, mother, and seven children, of whom the eldest (Charles 15) worked at Cavendish's Wine Stores where he earned 6/- a week. She occupied half the house the rent of which was 12/6 a week, the lodgers paid 6/- leaving them 6/6. The rent was paid up to date. Mrs. Lush said she her Husband's brother was a subscriber to the Hospital and had told her if at any time she wanted to attend he would give her a ticket, but she did not like to ask him. His address is — Mr S. Lush, 51 Petterdon Road. Insuff. Infn. Dr 378/IMSW/A/1/6/8a